Program Bimbingan Psiko-Sosio-Spiritual Berbasis Online Bagi Masyarakat Di Tengah Pandemi Covid-19 - Ahmad Razak; Ahmad Yasser Mansyur; Novita Maulidya Jalal (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. The Covid-19 pandemic has yet to show signs of ending. Covid-19 has had various impacts on the dynamics of people's lives. One of the impacts is psychological disorders which affect the inability of the community to manage emotions properly. Psycho-socio-spiritual guidance as a way to help society in dealing with psychological problems faced. This activity aims to: 1) increase public knowledge about psycho-socio-spiritual in responding to the Covid-19 pandemic. 2) increasing positive attitudes in managing emotions amid the Covid-19 pandemic. Participants in this activity were 80 Indonesians who experienced psychological disorders amid the Covid-19 pandemic who were selected by purposive sampling. The results of this activity 1) increased public knowledge about psycho-socio-spiritual in responding to the covid-19 pandemic. 2) Increased positive attitudes in managing emotions amid the Covid-19 pandemic